Grab a bite? Prices in the food away from home industry during the COVID-19 pandemic - Diego Solórzano (Banco de México, 2023)
The pandemic generated heterogeneous demand shocks in the food away from home industry's consumption channels: on-site and deliveries/takeaways. Hence, price adjustments by consumption channel could have also been different. This study examines dishes' prices intended to be consumed as deliveries, which come from an online food ordering and delivery platform in Mexico City (CDMX); as well as those aimed at on-site consumption, which are considered in CDMX's CPI. I document that during part of the period between April 2020 and March 2022 delivery prices grew at a faster rate than those for on-site consumption. This is consistent with the idea of positive demand shocks for delivery prices and negative for on-site prices. By March 2022, their cumulative price growth across both consumption channels was similar.
Keywords: C5; E30; E60; 330; Inflation; Nominal rigidities; Restaurants; Machine Learning